Vista View Corporation: Implementing a global manufacturing project in China - PAL, Subrata (Institutional Knowledge at Singapore Management University, 2013)
Vista View Corporation is a large American pharmaceutical company manufacturing and selling both prescription and over the counter eye care products, with branches in 50 countries. Since 2008, Vista View had been consolidating its business within its consumer products division to focus on emerging market growth potential and to tap into low cost manufacturing in China and India. As a major supply chain strategy for its eye drop product “Eyeglow”, Vista View had decided to consolidate major international market supply (i.e., markets other than North America, Africa and Europe) into China. The Eyeglow range of products were to be manufactured in China and supplied to South America, Asia, Middle East and Australia The China team had been working on a business case for transferring global Eyeglow (Vista View’s top selling over the counter eye drop product) manufacturing to China for the past six months. The business case showed that if global volumes were consolidated in China, the cost of goods could be brought down substantially. But Dave Woods, Vice President of Asia Supply knew that despite the business case being approved, he would have an uphill task executing this strategy. His boss, Mathew Gill, had asked him to come up with a detailed project plan for eyeglow manufacturing in China that would be presented at the Global Strategy Team meeting in New Jersey in the following month. He was wondering how he could ensure that his team would be able to come up with a realistic executable project plan, that they would be able to deliver within budget in 18 months.